2004
DOI: 10.1111/j.1524-4725.2004.30149.x
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Features in Primary Cutaneous Squamous Cell Carcinomas in Immunocompromised Patients Focusing on Organ Transplant Patients

Abstract: Our findings confirmed the association of ultraviolet radiation exposure with development of CSCC in OTR. The increased depth of the primary CSCC in OTR is surprising because these patients are followed closely for skin cancer compared with immunocompetent patients. The other morphologic features that were significantly more common in OTR may theoretically reflect not only the type of iatrogenic immunosuppression in these patients, but also other procarcinogenic effects of their medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 49 publications
4
61
0
Order By: Relevance
“…In the case of SCCs, spindle cell change appeared to be a feature associated with a more-aggressive course in RTRs in that 2 of the 3 tumors that recurred and metastasized were diffuse spindle cell lesions, whereas other features usually indicative of poor prognosis, including depth of invasion, perineural infiltration, and acantholysis, [21][22][23] were not more common. In contrast, in a large study comparing OTR and IC-SCCs, 29 a higher proportion of OTR-SCCs were classified as Broder's stage III/IV, were deeper, and had more acantholytic and infiltrative/neurotropic/desmoplastic change. Interpretation of this study and comparison with our own are complicated by the facts that the transplant population investigated were a mixture of renal, heart/heart-lung, and liver recipients, OTR and IC patients came from multiple clinical centers (number not specified), a mixture of primary and recurrent lesions were included, the presence alone rather than extent of acantholysis is recorded, and long-term follow-up is not provided.…”
Section: Correlation Of Histologic Features and Clinical Coursementioning
confidence: 76%
“…In the case of SCCs, spindle cell change appeared to be a feature associated with a more-aggressive course in RTRs in that 2 of the 3 tumors that recurred and metastasized were diffuse spindle cell lesions, whereas other features usually indicative of poor prognosis, including depth of invasion, perineural infiltration, and acantholysis, [21][22][23] were not more common. In contrast, in a large study comparing OTR and IC-SCCs, 29 a higher proportion of OTR-SCCs were classified as Broder's stage III/IV, were deeper, and had more acantholytic and infiltrative/neurotropic/desmoplastic change. Interpretation of this study and comparison with our own are complicated by the facts that the transplant population investigated were a mixture of renal, heart/heart-lung, and liver recipients, OTR and IC patients came from multiple clinical centers (number not specified), a mixture of primary and recurrent lesions were included, the presence alone rather than extent of acantholysis is recorded, and long-term follow-up is not provided.…”
Section: Correlation Of Histologic Features and Clinical Coursementioning
confidence: 76%
“…Smith et al 25 showed that cSCC in OTR had significantly higher rates of acantholytic changes, early dermal invasion, lymphovascular invasion, and increased tumor thickness. Traywick and O'Reilly 26 demonstrated that tumors in immunosuppressed patients are larger in size ([2-cm diameter) and have significantly more PNI and invasion of cartilage, fat, or bone.…”
Section: Discussionmentioning
confidence: 98%
“…Differentiation (grading) of SCC in OTR does not differ from SCC in the general population [4]. SCC in OTR presents more often with spindle cell morphology found in 20% of the lesions, and acantholysis [4,7]. Expression of cytokeratins (especially CK 5/6), p63 and CAM5.2 is particularly helpful for proving the epithelial origin of spindle cell SCC.…”
Section: Epithelial Skin Neoplasmsmentioning
confidence: 99%